1976
DOI: 10.2134/agronj1976.00021962006800020057x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chloride and Potassium on Corn Lodging1

Abstract: Ammonium chloride treatments were included on selected plots in a corn (Zea mays L.) field laboratory fertility study to determine whether or not reductions in lodging observed in previous years were due to chloride or potassium in the KCl treatments. Sixty‐four percent of the corn lodged in plots receiving no potassium and no chloride or chloride as NH4Cl, while lodging was only 16% with comparable KCl treatments. It is concluded that the reduction in lodging was due to potassium and not chloride.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Incidence of stalk rot was not influenced by Cl treatment in 1991, but there was a linear decrease (P = 0.07) in lodging with rate of Cl (Table 6). An evaluation by Liebhardt and Munson (1976), however, found no effect of Cl on lodging. In 1992, Cl rate resulted in a linear decrease in incidence of stalk rot.…”
Section: Stalk Rot and Lodgingmentioning
confidence: 87%
“…Incidence of stalk rot was not influenced by Cl treatment in 1991, but there was a linear decrease (P = 0.07) in lodging with rate of Cl (Table 6). An evaluation by Liebhardt and Munson (1976), however, found no effect of Cl on lodging. In 1992, Cl rate resulted in a linear decrease in incidence of stalk rot.…”
Section: Stalk Rot and Lodgingmentioning
confidence: 87%
“…A re-evaluation of this study by Liebhardt and Munson (1976) showed that K and not CI was responsible for delaying cellular senescence.…”
Section: Environmental Influence On Stalk Qualitymentioning
confidence: 70%
“…These results have been challenged by Martens and Arney (1967) who showed that KCl gave greater response than Cl~ alone (in NH^Cl form). Liebhardt and Munson (1976) reached the same conclusion, that the effect of KCl treatments is due to the K^, not the Cl~. The KCl treatment yielded 7.2 Mg ha"^ with 16% lodging, while both the NH^Cl and no K or CI treatments yielded 5.5 Mg ha~^ with 64% lodging.…”
mentioning
confidence: 64%